Factors Related to the Behavior of Using Styrofoam Container on Seblak Traders in Yogyakarta - Aris Yulianto; Isna Munawaroh; Dyah Suryani (Universitas Gorontalo, 2022)
Styrofoam is a material of polystyrene, still included in the plastic group and a styrene monomer. The danger of styrene monomers to health after long-term exposure is to cause headaches, fatigue, depression and anemia besides Styrofoam waste is a waste that is very difficult to decompose by nature. The purpose of this study was to determine the factors associated with the behavior of the use of Styrofoam containers in seblak traders in Umbulharjo and Gondokusuman Districts, Yogyakarta. This study used a cross sectional study. The research subjects were seblak trader which numbered 50 traders, the object of the research was the use of 50 samples of styrofoam containers. The research instrument is a questionnaire and checklist. Data analysis with univariate and bivariate analysis. The results showed that there was no relationship between age and the behavior of using Styrofoam containers in seblak traders (p = 0.543 >.05), there was no relationship between gender and the behavior of using Styrofoam containers in seblak traders (p = 0.252 > 0.05), there is no relationship of knowledge with the behavior of the use of Styrofoam containers in seblak traders (p = 0.123 >0.05), and there is an attitude relationship with the behavior of the use of Styrofoam containers in seblak traders (p = 0,001 <0.05). There is no relationship between age, gender, knowledge, and behavior of using styrofoam containers. There is a relationship between attitude and behavior of using styrofoam containers